The Tira de Tepechpan: Negotiating Place under Aztec and Spanish Rule - Diel, Lori Boornazian (University of Texas Press, 2008)
Created in Tepechpan, a relatively minor Aztec city in Central Mexico, the Tira de Tepechpan records important events in the city’s history from 1298 through 1596. Most of the history is presented pictographically. A line of indigenous year signs runs the length of the Tira, with images above the line depicting events in Tepechpan and images below the line recording events at Tenochtitlan, capital of the Aztec empire and later the seat of Spanish rule. Written annotations amplify some of the images. In this volume, which includes color plates of the entire Tira, Lori Boornazian Diel investigates the motives behind the creation and modification of the Tira in the second half of the sixteenth century. She identifies the Tira’s different contributors and reconciles their various histories by asking why these painters and annotators, working at different times, recorded the events that they did. Comparing the Tira to other painted histories from Central Mexico, Diel demonstrates that the main goal of the Tira was to establish the antiquity, autonomy, and prestige of Tepechpan among the Central Mexican city-states that vied for power and status in the preconquest and colonial worlds. Offering the unique point of view of a minor city with grand ambitions, this study of the Tira reveals imperial strategy from the grassroots up, showing how a subject city negotiated its position under Aztec and Spanish control.